The Effect of Teriparatide Treatment on Spinal Deformity Index in Severe Osteoporosis - Fatma Gül Ülkü Demir; Mustafa Çalış; Havva Talay Çalış; Kürşad Ünlühızarcı; Esra Sonbahar Bolat; Selçuk Mıstık (Galenos Yayinevi, 2019)
Objective:This study's purpose was to evaluate the efficacy of teriparatide (TPTD) therapy on back pain, quality of life, and spinal deformity index (SDI) in the presence of established postmenopausal osteoporosis.Materials and Methods:The mean ages of 21 patients with established osteoporosis were 72.43±4.06 years. The patients with L1-L4 mean vertebral and/or hip total T score -4 and less, and at least two vertebral and/or non-vertebral fractures, were included in the study. The patients received 20 microgram (μg)/day TPTD treatment and 800 IU/day vitamin D3 + 1200 mg/day calcium (Ca) treatment during six months. Biochemical parameters were examined before the treatment and sixth month controls. Visual analog scale (VAS) was used for back pain, short form 36 (SF-36) for quality of life, in addition, grading of vertebral fracture severity according to Genant method and SDI evaluation were performed.Results:The mean total alkaline phosphatase, uric acid, and 24-hour urinary Ca values of the patients demonstrated a statistically significant increase after TPTD treatment compared to the pre-treatment level (p<0.01, p<0.05, p<0.05; respectively). There was no statistically significant difference in other biochemical markers according to the pre-treatment. A statistically significant increase was observed in the L1-L4 bone mineral density of the patients (p<0.01). After the treatment, there was a statistically significant improvement in SF-36 and VAS values of the patients according to pre-treatment (p<0.01). A statistically significant increase was detected in SDI after TPTD treatment (p<0.01).Conclusion:It has been determined that the treatment of TPTD treatment improves back pain and quality of life by decreasing the risk of new fracture developments in advanced age group and in patients with multiple fractures, however, the expected increase in SDI is still continuing in the present fractures.